Electrocatalytic Activity of Novel Ball-Type Metallophthalocyanines with Trifluoro Methyl Linkages in Oxygen Reduction Reaction and Application as Zn-Air Battery Cathode Catalyst - ÖZKAYA, ALİ RIZA; ÖZER, METİN (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
A new series of functional compounds, (((perfluoropropane-2,2-diyl) bis (4, 1-phenylene)) bis (oxy))bridged ball-type metal-free and zinc(II), cobalt (II) and iron (II) metallophthalocyanines, behaving as the air catalyst in zinc-air batteries have been developed, and characterized with common spectroscopic methods. The catalyst composites were characterized by scanning electron microscopy (SEM), energy dispersive X-Ray analysis (EDS), and energy dispersive elemental mapping (EDS mapping). The catalytic activites of the dimeric type complexes on oxygen reduction reaction (ORR) have been evaluated by static and dynamic voltammetric techniques. In particular, iron (II) complex displayed spectacular catalytic activity with slightly more positive half-wave potential than that of the commercial Pt/C for ORR in alkaline media, mainly due to its distinctive cofacial molecular structure with dual redox-active metal centers. The electrocatalytic performance tests, carried out in a homemade Zn-air battery prototype, suggested that this complex can be used as an efficient ORR catalyst in this type of batteries. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Zn-air Battery; Phthalocyanine; Transition Metal; Electrocatalysis; Oxygen Reduction Reaction; GAS-SENSING PROPERTIES; IRON-PHTHALOCYANINE; ELECTROCHEMICAL PROPERTIES; METAL-FREE; GRAPHENE OXIDE; COBALT; PERFORMANCE; PORPHYRIN; ZINC(II); ELECTROREDUCTION